Analisis transportasi pengangkutan sampah dengan dump truck di PT XYZ pada area Pelabuhan Tanjung Perak dengan metode Dynamic programming - Remba, Angga Rizki Dolla; Pulansari, Farida (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The problem of urban waste in Indonesia is a problem that has not been completely solved, it also occurs in the Tanjung Perak Port area. This problem can be overcome by regulating the process of moving and transporting waste based on optimal routes. The purpose of this study is to analyze the waste transportation system in several Depots (TPS) in the Tanjung Perak Port area and compare the transportation cost needs in each waste transportation pattern to find the most optimal route. The stages carried out are to collect data on the distance of the Pool to each Depo/TPS, the distance between TPS, and the distance of each TPS to the Benowo Landfill. The application of the Dynamic programming Algorithm is used to determine the shortest distance, and calculate the minimum operational cost. The results of the study show that the Dynamic programming algorithm can determine the optimal route for the problem of waste transportation routes at each TPS at Tanjung Perak Port with the number of Dump trucks as many as 1 vehicle and the calculation of fuel cost needs per day of Rp.88,413,-.